Children of parents with different severities of mental health conditions have higher risk of somatic morbidity: a Danish nationwide register-based cohort study - Camilla Klinge Renneberg; René Børge Korsgaard Brund; Signe Heuckendorff; Bodil Hammer Bech; Kirsten Fonager (BMC, 2023)
Abstract Background Children with the most severe parental mental health conditions have an elevated risk of numerous adversities including somatic morbidity. However, there is no knowledge concerning physical health in most children affected by parental mental health conditions. Therefore, the aim was to examine the association between different severities of parental mental health conditions and somatic morbidity in children of different age-groups and further explore the combinations of maternal and paternal mental health conditions on child somatic morbidity. Methods In this register-based cohort study, we included all children born in Denmark between 2000-2016 and linked parents. Parental mental health conditions were categorised into four severity groups (no, minor, moderate, and severe). Somatic morbidity in offspring was categorised into broad disease categories corresponding to the International Classification of Diseases. We estimated the risk ratio (RR) using Poisson regression, of the first registered diagnosis in different age-groups. Results Of the around 1 million children in the study > 14.5% were exposed to minor parental mental health conditions and < 2.3% were exposed to severe parental mental health conditions. Overall, the analyses revealed a higher risk of morbidity in exposed children across all disease categories. The strongest association was observed for digestive diseases in children aged < 1 year exposed to severe parental mental health conditions (RR: 1.87 (95% CI: 1.74-2.00). Generally, the risk of somatic morbidity increased the more severe the parental mental health conditions. Both paternal and especially maternal mental health conditions were associated with a higher risk of somatic morbidity. The associations were strongest if both parents had a mental health condition. Conclusion Children with different severities of parental mental health conditions experience a higher risk of somatic morbidity. Although children with severe parental mental health conditions had the highest risk, children with minor parental mental health conditions should not be neglected as more children are exposed. Children with both parents having a mental health condition were the most vulnerable to somatic morbidity and maternal mental health conditions were more strongly associated with somatic morbidity than paternal. More support and awareness of families with parental mental health conditions is highly needed.